Transfer-free growth of graphene on Al2O3 (0001) using a three-step method. (May 2018) - Zhang, Chitengfei; Huang, Jin; Tu, Rong; Zhang, Song; Yang, Meijun; Li, Qizhong; Shi, Ji; Li, Haiwen; Zhang, Lianmeng; Goto, Takashi; Ohmori, Hitoshi
Abstract: The transfer process before graphene device fabrication could worsen the performance of graphene device greatly, so a transfer-free growth method for preparing graphene films is demanded urgently. Herein, we propose a novel three-step method to achieve transfer-free graphene films on Al2 O3 (0001) substrates. Cu (111) films and carbon source were co-deposited on α-Al2 O3 (0001) substrates by metal-organic chemical vapor deposition (MOCVD) at one step, then graphene was synthesis by a rapid annealing process, transforming the carbon source in copper into graphene films. Finally, a transfer-free graphene film with an ultra-smooth surface (∼3.49 nm) is achieved by etching the copper film on Al2 O3 (0001). Crystallographic characterization demonstrated the as-deposited Cu films show a nature of epitaxial single crystal, with a smooth surface (∼6.89 nm). Few layer graphene films (3–4 layers) with least defect concentration were grown at annealing time of 20 min. Graphical abstract: Image